Elephant fruit :The dispersal attributes of Balanites maughamii / Storme Viljoen - Viljoen, Storme (Department of Biological Sciences, 2015)
Endozoochorous plant species that have obligate dispersal mutualisms with megafauna are at risk of extinction because of the unique conservation threats associated with large animals. This study examines Balanites maughamii which appears to have similar dispersal attributes to Sclerocarya birrea and Balanites wilsoniana, both of which are considered to be obligate elephant fruits. Here, I emphasize the traits that make B. maughamii suitable for elephant dispersal and examine the cues required for seed germination. Large, fleshy fruits with a single, exceptionally hard seed which requires a crushing force of > 2.0 kN to promote germination are characteristic of this species. Using scent analysis of ripe fruits, the range of volatile that are responsible for the pungent odour were identified as being those which should function in mammal-attraction. Finally I examine the potential for long-distance dispersal by elephants using a gut passage time experiment, which revealed that elephants retain seed for approximately 48 hours, equating to a 4-8 km dispersal distance. Using fruit and seed bait stations to determine which other animals interact with B. maughamii, I found that small mammals may play a significant role in seed predation and that there is little evidence to suggest extensive secondary dispersal by rodents. These finding allude to the vulnerability of the long-term maintenance of B. maughamii in the absence of elephants, who appear to be their only legitimate disperser.